A Note on the Inner-Outer Iterative Method for Solving the Linear Equation Ax = b. (6th July 2020) - Zhang, Li-Tao; Zuo, Xian-Yu; Gu, Tong-Xiang; Wang, Yan-Ping; Zhang, Yi-Fan; Li, Jian-Lei; Li, Sheng-Kun
Abstract : Recently, Tian et al. [Computers and Mathematics with Applications, 75(2018): 2710-2722] came up with the inner-outer iterative method to solve the linear equation A x = b and studied the corresponding convergence of the method. In this paper, we improve the main results of the inner-outer method and get weaker convergence results. Moreover, the parameters can be adjusted suitably so that the convergence property of the method can be substantially improved.